IMPLEMENTASI INTEGRASI PENDIDIKAN KARAKTER PADA SEKOLAH ISLAM TERPADU (Studi Kasus di SMP Islam Terpadu Abu Bakar Yogyakarta) (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
Government to prioritize education is reflected in the character of the National Long- Term Development Plan 2005-2025 year, in response to the condition of the country in crisis multidimensional. Implementation on the ground is different from each agency and level of education, according to the Education Unit Level Curriculum and can be expanded according to the vision mission of the school. SIT (SMP IT Abu Bakar Yogyakartak) is a junior secondary school background in Islam since its inception more emphasis on the cultivation of values (character).While there are some people negative impression about Islam integrated schools such as the absence of the ceremony, do not want to respect the flag, etc.This research aims to describe the : 1) planning, 2) organization, 3) implementation, 4) monitoring and evaluation, 5) barriers and solutions to the implementation of character education programs in SMP IT Abu Bakar Yogyakarta. This research used a qualitative approach with descriptive analysis method case study design. Data was collected by: 1) interviews, 2) observation, 3) study the document. The data source consisted of the principal, vice-principal, part coordinator, counseling teacher, homeroom teachers, subject teachers, staff, employees and related documents. Data was analyzed by data reduction, data presentation, and conclusion. Checking the validity of the data was by triangulation.The results of the implementation of the integration of character education in SMP IT Abu Bakar Yogyakarta are : 1) planning on character education program conducted at the beginning of the school year and the beginning of the semester through the meeting with reference to the vision and mission of the school, 2) organizing programs vertical and horizontal through the highest office holder down with the person in charge at each field of activity, 3) implementation the programs through the stages of a) socialization to the academic community (teachers and staff), parents, students and the community through the mechanism of POMG, b) integrated in the process of learning, c) integrated in student activities, and through integrated school management, 4) monitoring and evaluation is scheduled and conducted periodically. Barriers and its solution are associated with the implementation of the integration of character education such as: a) the resistance of parents, teachers, and the community, b) the resistance of students, and c) the barries of the implementation.